Clinical Characteristics and Response to Therapy in Pediatric Systemic Lupus Erythematosus - Saima Fatima,Nasir Khan, Tabassum Bashir, Zahid Rashid, Tahir Mahmood,Khyal Muhammad, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Pediatric systemic lupus erythematosus (pSLE) is a rare but severe autoimmune disordercharacterized by heterogeneous clinical presentation and variable therapeutic response. Thisprospective observational study evaluated the clinical profile, laboratory parameters, and therapeutic outcomes